Información científica, biblioteca y conocimiento. - Gimeno Perelló, Javier (Revista General de Información y Documentación, 2001)
The advanced development of information technology has given rise to a considerable increase in the amount of information available. It is now neces sary to learn to sclect and use it correctly so that tbe user can transform. Infor madon centres, public and university libraries are challenged with undertaking informational education projects to broaden and improve the traditional user education services. tmportant practical cases undcrtaken by sorne libraries are detailed.
Keywords: Scientific information; Knowledge; Information users; Public libraries; University libraries; Information centres; User educarion; Information skills